The Influence of Tax Planning and Earnings Management on Tax Avoidance in Manufacturing Companies in the Industrial Sector Listed on the Indonesia Stock Exchange - Rahmawati, Titah; Mahwiyah, Mahwiyah (Sean Institute, 2025)
Taxes are a vital source of state revenue in Indonesia, yet efforts to optimize tax collection often face challenges due to corporate strategies aimed at reducing tax burdens. Among these strategies, tax planning and earnings management are frequently associated with tax avoidance practices that can undermine transparency and fiscal sustainability. Understanding how these mechanisms influence tax behavior is crucial to ensure corporate accountability and strengthen regulatory oversight. This study aims to examine the effect of tax planning and earnings management on tax avoidance among service companies listed on the Indonesia Stock Exchange. Using a quantitative descriptive analysis, the research evaluates both the individual and combined impacts of these financial strategies on corporate tax behavior. The findings show that tax planning has a significant but negative influence on tax avoidance, suggesting that structured tax planning reduces aggressive tax practices. In contrast, earnings management has a positive and significant effect on tax avoidance, indicating that firms engaging in earnings manipulation are more likely to minimize tax obligations. Furthermore, the combined analysis confirms that tax planning and earnings management jointly contribute significantly to variations in tax avoidance. These results highlight the complex dynamics between financial decision-making and tax compliance, emphasizing the importance of transparent reporting and regulatory control in curbing unethical tax practices.